HAMBATAN PERLINDUNGAN TERHADAP ANAK PEREMPUAN DI GHANA - Devi, Anggi Kurnia; Eriyanti, Linda Dwi; Yuniarti, Sri (Interdependence Journal of International Studies, 2024)
Tradition is an aspect of culture preserved and passed down from generation to generation. Tradition is also known as a concept that defines the identity and uniqueness of a community, which is also a source of security. Tradition is praised, glorified, and related to something good in a particular custom or area and is considered sacred. However, in Ghana there is a tradition called the Trokosi tradition. This tradition is also a cycle of sexual exploitation that society cannot break. Various protection efforts have been made by the Government of Ghana, INGOS, and even local community organizations, but this tradition is still being carried out today. By using the concept of feminism, this study wants to analyze the obstacles to efforts to protect girls who are victims of the Trokosi tradition in Ghana. The data used in this research is secondary data obtained from the research results or analysis from other parties directly involved in the form of news, journals, and books. With a radical feminist perspective, the author finds that the deep-rooted patriarchal culture has strengthened the trokosi tradition as the main factor inhibiting the protection of girls in Ghana.